Phenolic and flavonoid content with agro morphological characters of 12 accessions of Justica gendarussa grew in Indonesia - NELLY MARLIANI; I MADE ARTIKA; MOHAMAD RAFI; MUHAMAD SYUKUR; RONNY YUNIAR GALINGGING; WARAS NURCHOLIS (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Marliani N, Artika IM, Rafi M, Syukur M, Galingging RY, Nurcholis W. 2022. Phenolic and flavonoid content with agro morphological characters of 12 accessions of Justica gendarussa grew in Indonesia. Biodiversitas 23: 5101-5107. Justicia gendarussa Burm. f is a medicinal plant used in traditional and modern medicine. This study was conducted to determine the agro morphological characters, phenolic and flavonoid content of 12 accessions of J. gendarussa plants obtained from various locations in Indonesia and then grown in the same conditions and places. The agro morphological characteristics include plant height, number of leaves, number of branches, wet weight, and dry weight of leaves and stems. Total phenolic content (TPC) and total flavonoid content (TFC) were analyzed by spectrophotometric method. The results showed significant differences in the characters of 12 accessions of J. gendarussa (p<0.05). Accessions of BK4 (Bekasi 4) and KP (Kejayan Pasuruan) had the best agro morphological characteristics. Accessions of BK4 (Bekasi 4) and BG (Bogor) had the best growth rates. The highest TPC value was obtained from TG (Trenggalek) accession (0.752 mg GAE/g DW) and the highest TFC (1.899 mg QE/g DW from LK (Langkat) accession. The best accessions based on agro morphological characters were BK4 (Bekasi 4) and KP (Kejayan Pasuruan), and based on the content of polyphenols were TG (Trenggalek) and LK (Langkat). The accessions of BK4, BG, TG, and LK could be further developed into superior varieties of J. gendarussa.